2001
DOI: 10.1161/01.str.32.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cerebrovascular CO 2 Reactivity in CADASIL

Abstract: Background and Purpose-Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukencephalopathy (CADASIL) is a hereditary angiopathy caused by mutations in Notch3. Cerebral microvessels show an accumulation of granular osmiophilic material in the vicinity of degenerating vascular smooth muscle cells. To study cerebrovascular function in CADASIL, we performed measurements on cerebral hemodynamics by using transcranial Doppler sonography. Methods-Middle cerebral artery (MCA) mean blood flow velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(50 citation statements)
references
References 49 publications
6
43
0
1
Order By: Relevance
“…10 The pathological findings of the white matter of this case, such as the diffuse myelin loss and atrophy with mild gliosis and sparing of the subcortical U fibers and no evidence of leukodystrophy, are also compatible with this deduction. The significance of arterial SMC loss with respect to hemodynamic derangement in CADASIL is supported by the reduced cerebrovascular CO 2 reactivity associated with this disease 11 ; it has been shown that CO 2 reactivity is significantly lower in disabled than in nondisabled CADASIL individuals. This suggests that the severity and extent of SMC loss in the cerebral arteries progress at the shift from the nonsymptomatic to the symptomatic state.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…10 The pathological findings of the white matter of this case, such as the diffuse myelin loss and atrophy with mild gliosis and sparing of the subcortical U fibers and no evidence of leukodystrophy, are also compatible with this deduction. The significance of arterial SMC loss with respect to hemodynamic derangement in CADASIL is supported by the reduced cerebrovascular CO 2 reactivity associated with this disease 11 ; it has been shown that CO 2 reactivity is significantly lower in disabled than in nondisabled CADASIL individuals. This suggests that the severity and extent of SMC loss in the cerebral arteries progress at the shift from the nonsymptomatic to the symptomatic state.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that the severity and extent of SMC loss in the cerebral arteries progress at the shift from the nonsymptomatic to the symptomatic state. In addition, it has been reported that there is a reduction in blood flow to the cerebrum 4 and in the middle cerebral artery 11 in CADASIL, but these findings may merely reflect the final devastated state of the brain. Cerebrovascular reactivity to fluctuations not only in CO 2 but also in systemic blood pressure during the clinical course of CADASIL should be examined further.…”
Section: Discussionmentioning
confidence: 99%
“…46 Functional neuroimaging studies have provided evidence of compromised cerebral hemodynamics in CADASIL patients; studies of cerebrovascular reactivity, as determined by measurement of CBF changes after exposure to inhaled CO 2 or injected acetazolamide, indicate that cerebral blood vessels are dysfunctional in CADASIL patients. 70,71 Notably, an association was reported between a lower cerebrovascular reactivity at baseline and a larger increase in WMHs at follow-up, suggesting a role for impaired cerebrovascular reactivity in progression of whitematter lesions. Positron emission tomography studies have documented a significant decrease in CBF in the white matter, consistent with a chronic ischemia of white matter or decreased demand for oxygen and blood supply consequent upon having fewer normal cells to supply.…”
Section: Pathophysiology Of White-matter Injury In Small Vessel Diseasementioning
confidence: 99%
“…At the cerebral level, they are presumably responsible for a decrease in basal perfusion and reduction of hemodynamic reserve (Chabriat et al, 2000;Pfefferkorn et al, 2001). In vitro, abnormal vasoconstrictor responses to angiotensin II and noradrenaline have been detected in arteries of CADASIL patients (Hussain et al, 2004).…”
Section: Introductionmentioning
confidence: 99%